The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1038/s41598-022-26847-y
|View full text |Cite
|
Sign up to set email alerts
|

Fecal microbiota composition affects in vitro fermentation of rye, oat, and wheat bread

Abstract: Fermentation of dietary fiber by gut microbes produces short-chain fatty acids (SCFA), but fermentation outcomes are affected by dietary fiber source and microbiota composition. The aim of this study was to investigate the effect of two different fecal microbial compositions on in vitro fermentation of a standardized amount of oat, rye, and wheat breads. Two human fecal donors with different microbial community composition were recruited. Bread samples were digested enzymatically. An in vitro fermentation mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 41 publications
1
3
0
Order By: Relevance
“…However, after 62 24 h the initially Prevotella-dominated inocula was still dominated by Prevotella in oat and wheat substrates, whereas in rye substrate the genus Subdoligranulum dominated. Similarly to the study by , they also found that the Bacteroides-dominated inocula had a more diverse composition after 24 h compared with the Prevotella-dominated inocula (Pirkola et al 2023). Thus it is not clear why consumption of rye would promote Prevotella and in fact it does not consistently do so.…”
Section: Factors Possibly Affecting Abundance Of Prevotella and Bacte...supporting
confidence: 65%
See 3 more Smart Citations
“…However, after 62 24 h the initially Prevotella-dominated inocula was still dominated by Prevotella in oat and wheat substrates, whereas in rye substrate the genus Subdoligranulum dominated. Similarly to the study by , they also found that the Bacteroides-dominated inocula had a more diverse composition after 24 h compared with the Prevotella-dominated inocula (Pirkola et al 2023). Thus it is not clear why consumption of rye would promote Prevotella and in fact it does not consistently do so.…”
Section: Factors Possibly Affecting Abundance Of Prevotella and Bacte...supporting
confidence: 65%
“…In the same study, diversity in the Bacteroides cultures was higher after 24 h than in the Prevotella cultures, where one Prevotella OTU outcompeted other major taxa when fermenting the substrates. Another similar in vitro study examining fermentation and microbial shifts in inocula of human fecal origin dominated by either Prevotella or Bacteroides using rye, oat or wheat breads as substrates did likewise observe faster fermentation rate in the Prevotelladominated inoculum for all substrates (Pirkola et al 2023). However, after 62 24 h the initially Prevotella-dominated inocula was still dominated by Prevotella in oat and wheat substrates, whereas in rye substrate the genus Subdoligranulum dominated.…”
Section: Factors Possibly Affecting Abundance Of Prevotella and Bacte...mentioning
confidence: 65%
See 2 more Smart Citations